Pengaruh Pola Asuh Kristen dan Engagement Learning Terhadap Minat Memahami Firman Tuhan Kaum Muda GBI ROCK Bukit Pujian Sumba Barat. - Diana, Sara Febi; Susanti, Lidia (STIPAK Malang, 2024)
Abstract: Today, in the midst of the conditions demanded by the era, young people need a relevant and correct forum or community, one of which is through religious education in the church. It is the duty of Christian religious educators to save young people from the inequality of existing conditions. Most spiritual leaders face similar challenges as young people who are not interested in how to deliver sermons, lack interest in learning God's Word and other distractions. This research is a quantitative research using quasi-experimental method with a sample of 55 young people at GBI ROCK Bukit Pujian Waikabubak-West Sumba. Data analysis measures the relationship between variables using correlation tests and the magnitude of influence between variables. Based on the results of this study, Christian parenting and engagement learning are highly recommended to be applied in youth worship. Based on the explanation of the results of research on the influence of Christian parenting and engagement learning on the interest in learning God's word of young people GBI ROCK Bukit Pujian Waikabubak, it can be concluded as follows: First, there is a value between Christian parenting and the interest of young people learning God's word at GBI ROCK Bukit Pujian Waikabubak is known to have a strong relationship with a value of 0.565. This means that the stronger the parenting style used, the stronger the interest that young people have in learning God's words. Second, there is a value between engagement learning and the interest of young people in learning God's word at GBI ROCK Bukit Pujian Waikabubak is also known to have a very strong relationship, with a value of 0.638. This means that the stronger the engagement learning used, the stronger the interest that young people have in learning God's word at GBI ROCK Bukit Pujian Waikabubak. Third, the magnitude of the influence of Christian parenting and engagement learning on the interest of young people in learning God's word is known by 55.6% or with an R Square value of 0.556. In other words, most or 55.6% of young people's interest in learning God's word at GBI ROCK Bukit Pujian Waikabubak is influenced by Christian parenting and engagement learning.